ПОЛЯРИЗАЦИОННЫЕ СВОЙСТВА КВАЗАРА 3С273 - Чуприков, A. А. (Одеські астрономічні публікації, 2011)
Results of processing of the VLBA observational data of 2008 are presented. Our interest is well known quasar 3C273. Polarization maps are presented. Technologies of processing of polarization VLBA data as well as results of usage of such methods for VLBA data processing are discussed.